Serum alarmin S100A8/S100A9 levels and its potential role as biomarker in myocarditis - Irene Müller; Thomas Vogl; Uwe Kühl; Alexander Krannich; Aron Banks; Tobias Trippel; Michel Noutsias; Alan S. Maisel; Sophie vanLinthout; Carsten Tschöpe (ESC Heart Failure, 2020)
Abstract Aims The alarmin S100A8/S100A9 (S100A8/A9) is released by activated monocytes/macrophages and neutrophils in the setting lymphocytic myocarditis (MC). We recently demonstrated its therapeutic potential in experimental acute MC. Now, we investigated the diagnostic relevance of S100A8/A9 serum levels in patients with suspected acute and chronic MC and in patients with heart failure without cardiac inflammation. Methods and Results Serum S100A8/A9 levels were analysed in patients with a recent onset of MC [≤ 30 days, n = 32; ejection fraction (EF): 45.4 ± 12.9%], dilated cardiomyopathy patients with inflammation (n = 112; EF: 29.0 ± 11.4%), or without inflammation (n = 58; EF: 26.6 ± 9.3%), and controls (n = 25; EF: 68.5 ± 4.6%), by using specific ELISAs. Blood samples were collected at Time Point 1 (T1), where also endomyocardial biopsies (EMBs) were withdrawn. Patients with a recent onset of MC showed a 4.6‐fold increase in serum S100A8/A9 levels vs. controls (MC: 1948 ± 1670 ng/mL vs. controls: 426 ± 307 ng/mL; P < 0.0001). Serum S100A8/A9 correlated with the disease activity, represented by EMB‐derived counts of inflammatory cells (CD3: r = 0.486, P = 0.0047, lymphocyte function‐associated antigen‐1: r = 0.558, P = 0.0009, macrophage‐1 antigen: r = 0.434, P = 0.013), the EMB mRNA levels of S100A8, S100A9 (r = 0.541, P = 0.002), and left ventricular ejection fraction (LVEF: r = 0.498, P = 0.0043). EMB immunofluorescence co‐stainings display macrophages/monocytes and neutrophils as the main source of S100A8 and S100A9 in recent onset MC. The diagnostic value of serum alarmin levels (cut‐off 583 ng/mL) was characterized by a specificity of 92%, a sensitivity of 90.6%, positive predictive value of 93.5%, negative predictive value of 88.5%, and an accuracy of 0.949 (95% confidence interval [0.89–1]). In a subgroup of MC patients, S100A8/A9 serum levels and EMBs at T1 (n = 12) and a follow‐up visit (T2, n = 12, mean follow‐up 8.5 months) were available. A fall of serum S100A8/A9 (T1: 2208 ± 1843 ng/mL vs. T2: 888.8 ± 513.7 ng/mL; P = 0.00052) was associated with a reduced cardiac inflammation (CD3 T1: 70.02 ± 107.4 cells per square millimetre vs. T2: 59.18 ± 182.5 cells per square millimetre; P = 0.0342, lymphocyte function‐associated antigen‐1 T1: 133.5 ± 187.1 cells per square millimetre vs. T2: 74.12 ± 190.5 cells per square millimetre; P = 0.0186, and macrophage‐1 antigen T1: 132.6 ± 129.5 cells per square millimetre vs. T2: 54.41 ± 65.16 cells per square millimetre; P = 0.0015). Serum S100A8/A9 levels were only slightly increased in patients within the chronic phase of MC and in heart failure patients without inflammation vs. controls. Conclusions Serum S100A8/A9 might serve as an additional tool in the diagnostic workup of suspected acute MC patients.